Blocking the CTLA-4 and PD-1 pathways during pulmonary paracoccidioidomycosis improves immunity, reduces disease severity, and increases the survival of infected mice - Preite, Nycolas Willian; Borges, Bruno Montanari; Kaminski, Valéria de Lima; Ayupe, Marina Caçador; Gonçalves, Leonardo Mandu; dos Santos, Bianca Vieira; Fonseca, Dennyson Leandro M.; Filgueiras, Igor Salerno; Salgado, Caio Loureiro; Muxel, Sandra Marcia; Cabral-Marques, Otavio; da Fonseca, Denise Morais; et al. (Frontiers in Immunology, 2024)
Immune checkpoint pathways, i.e., coinhibitory pathways expressed as feedback following immune activation, are crucial for controlling an excessive immune response. Cytotoxic T lymphocyte antigen-4 (CTLA-4) and programmed cell death protein-1 (PD-1) are the central classical checkpoint inhibitory (CPI) molecules used for the control of neoplasms and some infectious diseases, including some fungal infections. As the immunosuppression of severe paracoccidioidomycosis (PCM), a chronic granulomatous fungal disease, was shown to be associated with the expression of coinhibitory molecules, we hypothesized that the inhibition of CTLA-4 and PD-1 could have a beneficial effect on pulmonary PCM. To this end, C57BL/6 mice were infected with Paracoccidioides brasiliensis yeasts and treated with monoclonal antibodies (mAbs) α-CTLA-4, α-PD-1, control IgG, or PBS. We verified that blockade of CTLA-4 and PD-1 reduced the fungal load in the lungs and fungal dissemination to the liver and spleen and decreased the size of pulmonary lesions, resulting in increased survival of mice. Compared with PBS-treated infected mice, significantly increased levels of many pro- and anti-inflammatory cytokines were observed in the lungs of α-CTLA-4-treated mice, but a drastic reduction in the liver was observed following PD-1 blockade. In the lungs of α-CPI and IgG-treated mice, there were no changes in the frequency of inflammatory leukocytes, but a significant reduction in the total number of these cells was observed. Compared with PBS-treated controls, α-CPI- and IgG-treated mice exhibited reduced pulmonary infiltration of several myeloid cell subpopulations and decreased expression of costimulatory molecules. In addition, a decreased number of CD4+ and CD8+ T cells but sustained numbers of Th1, Th2, and Th17 T cells were detected. An expressive reduction in several Treg subpopulations and their maturation and suppressive molecules, in addition to reduced numbers of Treg, TCD4+, and TCD8+ cells expressing costimulatory and coinhibitory molecules of immunity, were also detected. The novel cellular and humoral profiles established in the lungs of α-CTLA-4 and α-PD-1-treated mice but not in control IgG-treated mice were more efficient at controlling fungal growth and dissemination without causing increased tissue pathology due to excessive inflammation. This is the first study demonstrating the efficacy of CPI blockade in the treatment of pulmonary PCM, and further studies combining the use of immunotherapy with antifungal drugs are encouraged.